2008
DOI: 10.1111/j.1467-9361.2008.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

TAR Panel Unit Root Tests and Real Convergence

Abstract: The authors propose a new panel data methodology to test real convergence in a non-linear framework. This extends the existing methods by combining three approaches: the threshold model, the panel data unit root tests, and the computation of critical values by bootstrap simulation. The authors apply their methodology to the per capita outputs of a total of 15 European countries, including some of the East European countries that have recently joined the EU. Copyright � 2008 The Authors. Journal compilation � 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 13 publications
0
46
0
8
Order By: Relevance
“…In this study, by employing the first approach, the existence of a convergence between the daily returns of cryptocurrencies are analyzed through the panel nonlinear TAR method. This method was developed by Beyaert and Camacho (2008) and was applied for the 12 European countries in order to determine whether their incomes are convergence. They found that there was convergence of income among 9 high-income countries but that when 3 low-income countries were included in the group, the convergence did not occur.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, by employing the first approach, the existence of a convergence between the daily returns of cryptocurrencies are analyzed through the panel nonlinear TAR method. This method was developed by Beyaert and Camacho (2008) and was applied for the 12 European countries in order to determine whether their incomes are convergence. They found that there was convergence of income among 9 high-income countries but that when 3 low-income countries were included in the group, the convergence did not occur.…”
Section: Methodsmentioning
confidence: 99%
“…Based on findings also it is tried to developed suggestions for the investors who will form portfolios through these cryptocurrencies. Beyaert and Camacho (2008), examined the existence of a convergence in terms of national income per capita among European Union countries by nonlinear TAR unit root test for 1950-2004 period. As a result of the analysis, it was determined that there was convergence of income among 15 EU member countries, but the convergence disappeared when Eastern European countries are included in this group.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we use a heteroskedasticity-autocorrelation consistent Lagrange multiplier (LM) test and compute the p-values by a bootstrap method proposed by Hansen (1996). Second, we test whether the countries converge or diverge using a threshold autoregressive unit root test proposed by Caner and Hansen (2001) and extended for the panel-data model by Beyaert and Camacho (2008). In Model 3, if s1 = s2 = 0 then we say that the countries diverge.…”
Section: Threshold Regressions and Club Convergencementioning
confidence: 99%
“…Asterisks indicate a significance level of *1%, **5%, and ***10% at which the null of linearity is rejected. Dagger-reject the null of a unit root at the † 1% significance level based on the threshold autoregressive unit root test introduced by Caner and Hansen (2001) and extended for the panel-data model by Beyaert and Camacho (2008). Results for both tests are calculated using standard heteroskedasticity and autocorrelation corrected estimators.…”
Section: Evidence From Threshold Regression Models 421 Testing For mentioning
confidence: 99%
“…Utilizou-se uma versão adaptada da rotina em Gauss disponibilizada por esses autores na realização destes testes. e covariância utilizada por Beyaert e Camacho (2008), rejeitou-se a hipótese nula de não integração entre as séries de preço analisadas, conforme a Tabela 3. Esse resultado indica um processo de convergência entre as séries de preço de tomate nos 13 mercados analisados.…”
Section: Estimação Do Modelo Econométricounclassified